2019
DOI: 10.1002/ijc.32577
|View full text |Cite
|
Sign up to set email alerts
|

Family history of prostate cancer and the incidence of ERG‐ and phosphatase and tensin homolog‐defined prostate cancer

Abstract: Family history is among the strongest known risk factors for prostate cancer (PCa). Emerging data suggest molecular subtypes of PCa, including two somatic genetic aberrations: fusions of androgen‐regulated promoters with ERG and, separately, phosphatase and tensin homolog (PTEN) loss. We examined associations between family history and incidence of these subtypes in 44,126 men from the prospective Health Professionals Follow‐up Study. ERG and PTEN status were assessed by immunohistochemistry. Multivariable com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…A transcriptome‐wide association study by Emami et al 29 observed a positive correlation between imputed TMPRSS2 expression levels in normal prostate tissue (as predicted by germline cis ‐expression quantitative trait loci) and ERG expression in TMPRSS2:ERG fusion‐positive tumour samples 29 . Furthermore, in a prospective study of 888 PrCa cases from the Health Professionals Follow‐up Study, Hashim et al 30 found that family history was strongly associated with ERG‐positive staining in tumour tissue—a surrogate for TMPRSS2:ERG fusion status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A transcriptome‐wide association study by Emami et al 29 observed a positive correlation between imputed TMPRSS2 expression levels in normal prostate tissue (as predicted by germline cis ‐expression quantitative trait loci) and ERG expression in TMPRSS2:ERG fusion‐positive tumour samples 29 . Furthermore, in a prospective study of 888 PrCa cases from the Health Professionals Follow‐up Study, Hashim et al 30 found that family history was strongly associated with ERG‐positive staining in tumour tissue—a surrogate for TMPRSS2:ERG fusion status.…”
Section: Discussionmentioning
confidence: 99%
“…It thus appears that the frequency of fusion events in PcTas9 is considerably higher than the frequency normally observed in Caucasian tumour cohorts (~40%–50%) 3–6 and suggests an underlying inherited predisposition to the formation of these events in this family. In fact, there is now a strong body of evidence supporting this theory, 3,12–15 including two recent and very diverse studies 29,30 . A transcriptome‐wide association study by Emami et al 29 observed a positive correlation between imputed TMPRSS2 expression levels in normal prostate tissue (as predicted by germline cis ‐expression quantitative trait loci) and ERG expression in TMPRSS2:ERG fusion‐positive tumour samples 29 .…”
Section: Discussionmentioning
confidence: 99%